KEPENTINGAN SURIAH MENJALIN HUBUNGAN DIPLOMATIK DENGAN LEBANON (2008) - Widodo, Aridianto; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research describes about syria interests in Lebanon in conducting diplomatic relations. In the beginning, Syria did not agree with the establishment of the Lebanese State because it leads to reduced part of Syrian territory. Syria initially determined not to open formal diplomatic relations with Lebanon. In 2008 Syria began to open the way for diplomatic relations. The attitude of Syria in opening diplomatic relations with Lebanon certainly has its own importance.This research uses a realist perspective. Where the realist focused that the State is a major actor in international politics. Syria opened relations with Lebanon to achieve the interests of his country. In this paper, the author uses the analysis of the level of the nation state that focuses on the discussion of the diplomatic relations forged by Syria in Lebanon. The author uses the method of library research to collect data, the data collection methods of books, journals, articles, internet and other supporting media.The results of this research indicate that Syria has a national interest in Lebanon. Therefore, syria opened diplomatic relations with Lebanon which will provide benefits in syria, namely in the field of military security, and regional integration.Keywords :diplomatic relations, national interest, regional integration